DDQ-promoted mild and efficient metal-free oxidative α-cyanation of N-acyl/sulfonyl 1,2,3,4-tetrahydroisoquinolines - Kim, Hong Pyo; Yu, Heesun; Kim, Hyoungsu; Kim, Seok Ho; Lee, Dongjoo (Molecules, 2018)
A mild and highly efficient metal-free oxidative α-cyanation of N-acyl/sulfonyl 1,2,3,4-tetrahydroisoquinolines (THIQs) has been accomplished at an ambient temperature via DDQ oxidation and subsequent trapping of N-acyl/sulfonyl iminium ions with (n-Bu)3SnCN. Employing readily removable N-acyl/sulfonyl groups as protecting groups rather than N-aryl ones enables a wide range of applications in natural product synthesis. The synthetic utility of the method was illustrated using a short and efficient formal total synthesis of (±)-calycotomine in three steps.
Keywords: Catalysis; Cyanates; Oxidation-Reduction; Oxidative Stress; Tetrahydroisoquinolines; C(sp3)-H activation; Oxidation; Tetrahydroisoquinoline; α-cyanation